Trade Wars and Tariff Policies: Long-Term effects on Global Trade and Economic Relationship - Angwaomaodoko, Ejuchegahi Anthony (Business and Economic Research, 2024)
Trade wars and Tariff policies have become serious concerns defining and affecting global trade and economic relations in the 21st century. These policies characterized by the use of tariffs and other trade barriers have impacted the world beyond just the economic or financial effect between countries involved. The paper focuses on the long-term effect of trade wars and tariff policies on global trade and economic relationship between countries. Using historical and modern trade war scenarios such as USA-China trade war, the study indicates that disruption of global supply chain, volatility of financial market, and impact on specific sectors of the country economy such as agriculture are some of the long-term impacts of these policies on global trade. In terms of the impact on economic relationship between countries, the study highlights creation of new trade agreements and diversification of trade partnership as possible effects on economic relationship between countries. It is therefore imperative for countries to diversify their trade relationship by adopting initiatives against the effects of trade war. The study concludes that while national measures could bring some political and economic results in the short term, it is important to note that global prosperity cannot be long-lasting without cooperative and stable international trade policies.